2018
DOI: 10.1111/ajt.14767
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II, double-blind, placebo-controlled study assessing safety and efficacy of C1 esterase inhibitor for prevention of delayed graft function in deceased donor kidney transplant recipients

Abstract: Delayed graft function (DGF) is defined as need for dialysis early posttransplant. DGF is related to ischemia-reperfusion injury (IRI) that diminishes allograft function and may be complement dependent. Here, we investigate the ability of C1 esterase inhibitor (C1INH) to prevent IRI/DGF in kidney transplant recipients. Seventy patients receiving deceased donor kidney transplants at risk for DGF were randomized to receive C1INH 50 U/kg (#35) or placebo (#35) intraoperatively and at 24 hours. The primary end poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 27 publications
0
61
0
Order By: Relevance
“…However, clinical data on the protective effect of C1 inhibition in the context of IRI and DGF are limited. Jordan et al recently published the results of a phase I/II trial showing that patients receiving C1INH required fewer dialysis sessions in weeks 2‐4 posttransplant and had superior renal function 12 months after surgery; this effect was most significant in those receiving low‐quality grafts. These encouraging results support complement blockade in the peritransplant period as a valid and attractive approach to protect kidneys from IRI, prevent dysfunction, and improve long‐term renal function after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical data on the protective effect of C1 inhibition in the context of IRI and DGF are limited. Jordan et al recently published the results of a phase I/II trial showing that patients receiving C1INH required fewer dialysis sessions in weeks 2‐4 posttransplant and had superior renal function 12 months after surgery; this effect was most significant in those receiving low‐quality grafts. These encouraging results support complement blockade in the peritransplant period as a valid and attractive approach to protect kidneys from IRI, prevent dysfunction, and improve long‐term renal function after transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, DGF is relevant as it has been associated with negative recipient outcomes (Butala et al, 2013;Fonseca et al, 2015;McLaren et al, 1999;Tapiawala et al, 2010;Yarlagadda et al, 2009). First and foremost, DGF increases resource consumption, total cost of care, and emotional distress (Buchanan et al, 2008;Jordan et al, 2018;Mannon, 2018;Serrano et al, 2018;Zens et al, 2018). In addition, results of a large systematic review and metaanalysis of 33 studies have suggested that DGF is associated with a 38% higher risk of acute rejection and 41% increased risk of graft loss compared to recipients without DGF at 3.2 years of follow-up (Yarlagadda et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…C1‐INH regulates several pathways which contribute to both acute and chronic graft injuries. Extensive data from animal models, and a recent human trial by Jordan et al suggest that C1‐INH ameliorates IRI 49 . Subsequently, the authors assessed the long‐term, 3.5 years outcomes of patients treated with C1INH vs placebo and demonstrated a sustained improvement in eGFR for C1INH‐treated patients.…”
Section: Therapeutic Approaches To Treatment Of Amrmentioning
confidence: 99%